RELATIONSHIP BETWEEN SELF-CONFIDENCE AND ACADEMIC SUCCESS - Sabani, Havva; Saban, Yasemin (International Scientific Journal Vision, 2022)
Self-confidence is defined as one's self-confidence. Being at peace with oneself, accepting himself as he is, namely, it's a positive sense of oneself. Self-confidence is important for an individual's health and psychological well-being. Having a healthy self-confidence helps to be successful in personal and professional life. Self-confidence is important to school success because confident children believe they can learn new things, overcome difficulties, and make decisions on their own without outside influences. Lack of self-confidence constitutes a major problem that causes failure in school and other areas of life. Children who have developed healthy self-confidence find themselves sufficient in both lessons and extracurricular subjects. They feel confident in achieving something, and they strive to find solutions. The aim of this research paper is to examine the relationship between self-confidence and academic success.